Beginning power BI : a practical guide to self-service data analytics with Excel 2016 and Power BI desktop - Clark, Dan, 1963- (Apress, 2017)
Analyze your company's data quickly and easily using Microsoft's latest tools. Build scalable and robust data models to work from. Learn to clean and combine different data sources effectively. Create compelling visualizations and share them with your colleagues. Author Dan Clark takes you through each topic using step-by-step activities and plenty of screen shots to help familiarize you with the tools. This second edition includes new material on advanced uses of Power Query, along with the latest user guidance on the evolving Power BI platform. Beginning Power BI is your hands-on guide to quick, reliable, and valuable data insight. What You Will Learn: Simplify data discovery, association, and cleansing Create solid analytical data models Create robust interactive data presentations Combine analytical and geographic data in map-based visualizations Publish and share dashboards and reports.
Includes index.
Keywords: Microsoft Excel (Computer file); Microsoft PowerPivot (Computer file); Business intelligence -- Computer programs.; Information visualization -- Computer programs.; Business -- Data processing.; Visual analytics.; elektronické knihy; electronic books